β-sitosterol and gentisic acid loaded 1,2-dipalmitoyl-sn-glicero-3-phosphocholine liposomal particles - Aleksandra A. ovanović; Bojana D. Balanč; Ajda Ota; Verica B. Djordjević; Katarina P. Šavikin; Viktor A. Nedović; Nataša Poklar Ulrih (Journal of Engineering & Processing Management, 2019)
The aim of the present study was the examination of the impact of β-sitosterol and gentisic acid on characteristics of 1,2-dipalmitoyl-sn-glicero-3-phosphocholine (DPPC) liposomal particles: (a) bilayer permeability (fluorescence spectroscopy), (b) particle size, polydispersity index (PDI) and zeta potential (photon correlation spectroscopy) and (c) thermal properties (differential scanning calorimetry). ?-sitosterol has induced the increase of liposomal bilayer rigidity, due to rearranging of the phospholipids chains, while gentisic acid has enhanced the membrane fluidity, due to the reduced orderliness and the increase of phospholipids dynamics. The inclusion of β-sitosterol in liposomes has caused statistically significant increase of particle diameter and PDI, while the encapsulation of gentisic acid did not have influence on particle size distribution. Apart from that, the presence of β-sitosterol has resulted in the significant zeta potential increase, thus better stability of liposomal spheres (in the absence and in the presence of gentisic acid). β-sitosterol has decreased main transition temperature (Tm) and phase transition enthalpy (∆H), and caused the disappearance of the pre-transition peak as well, whereas the presence of gentisic acid has produced a slight decrease in Tm and increase of ∆H. Therefore, gentisic acid had more favourable, stabilizing interactions with phospholipids than β-sitosterol. Thus, it can be drawn a conclusion that β-sitosterol is located in the bilayer interior between phospholipids acyl chains, and gentisic acid is incorporated near the outer leaflet of phospholipid membrane, next to the polar head groups. β-sitosterol and gentisic acid loaded DPPC liposomal particles have potential to be used in food and pharmaceutical products, due to the important individual and possible synergistic beneficial health properties of β-sitosterol and gentisic acid.
Keywords: β-sitosterol; gentisic acid; liposomes; permeability